Understanding Intentions and Aspirations of Nepali Migrant Returnees: A Structural Equation Modeling Study - Lawaju, Purnima; Devkota, Niranjan; Panthi, Hemanta (International Research Journal of MMC, 2025)
Background: Labor migration is a movement of people from one country to the other country for employment opportunities. Labor migration is the term used to describe the exodus of Nepali laborers to other nations in pursuit of work, mostly due to financial need and work opportunities. The study focuses on foreign migrant workers who migrate from their native countries in search of better living conditions and incomes, as well as because of limited employment prospects and economic challenges. Methods: A Descriptive and explanatory research design is used in this study. 403 return migrants were taken as a sample by using purposive sampling method. Theory of Economic of Labor is used. Structured questionnaires were used to collect data and PLS-SEM was used to analyze the data. Both descriptive and inferential statistics were used to evaluate the data. Findings: The study shows mostly male are the migrant returnees from age range 30 to 40. Major variables to affect return decision of migrants are family obligation, psychological factors and Skill, development and career opportunity in home country. Majority of the people migrate for better work opportunities and to improve economic conditions. Mostly migrants faced the challenges like low wages, cultural differences and home sickness in host country which can be solved by fair wage rate, welcoming environment in host county, proper Nepalese agencies to help foreign migrants. Conclusions: The study emphasizes how family ties, psychological aspects, and the chances for skill development in their own country all play a role in the decision of many men to travel to and return to Nepal. Implications: This analysis and findings will help the Ministry of Labor, International Labor Organization, and Nepal Labor Market, local government, and researcher on the similar field, professionals and future students.